DAMPAK KERENTANAN SOSIAL PADA ATRATEGI LIVELIHOODS RUAH TANGGA PEREPUAN PESERTA UPPKS DI KECAATAN NGAPILAN KOTA YOGYAKARTA - Kurniyati, Nany Noor; Utami, Kristiana Sri (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2014)
Social studies of UPPKS programs in Ngampilan Subdistrict are rarely held. The incomes of female group members of UPPKS depend on the program activities. The government policy which involves the increasing prices of daily needs and other household commodities causes the low ability of women in overcoming their life problems so that they are susceptible to poverty. It is a descriptive qualitative research, a research which collects and describes data and presents the real results without trying to make conclusion for public or generalization. The data collection has been through in-depth interviews, observations and document studies. The research will describes the household social economic condition of female group members of UPPKS in Ngampilan Sub district of Yogyakarta City and the strategy of survival. Identify the vulnerability indicators in building the strength of UPPKS female members in Ngampilan Sub district in Yogyakarta City,identify the institution models which is potential to decrease the vulnerability and identify risk types in any program activities.